Overexpression of the STE4 gene leads to mating response in haploid Saccharomyces cerevisiae. - Whiteway, M (1990)
The STE4 gene of Saccharomyces cerevisiae encodes the beta subunit of the yeast pheromone receptor-coupled G protein. Overexpression of the STE4 protein led to cell cycle arrest of haploid cells. This arrest was like the arrest mediated by mating pheromones in that it led to similar morphological changes in the arrested cells. The arrest occurred in haploid cells of either mating type but not in MATa/MAT alpha diploids, and it was suppressed by defects in genes such as STE12 that are needed for pheromone response. Overexpression of the STE4 gene product also suppressed the sterility of cells defective in the mating pheromone receptors encoded by the STE2 and STE3 genes. Cell cycle arrest mediated by STE4 overexpression was prevented in cells that either were overexpressing the SCG1 gene product (the alpha subunit of the G protein) or lacked the STE18 gene product (the gamma subunit of the G protein). This finding suggests that in yeast cells, the beta subunit is the limiting component of the active beta gamma element and that a proper balance in the levels of the G-protein subunits is critical to a normal mating pheromone response.